2017
DOI: 10.1038/s41598-017-13925-9
|View full text |Cite
|
Sign up to set email alerts
|

Reference genes validation in Phenacoccus solenopsis under various biotic and abiotic stress conditions

Abstract: Real-time PCR (RT-qPCR) expression analysis is a powerful analytical technique, but for normalization of data requires the use of stable reference genes. However, suitable reference genes are still not known in the case of Phenacoccus solenopsis under variable experimental treatments. The present study focused on the identification of stable housekeeping genes as a reference for analysis under different abiotic and biotic factors in P. solenopsis. We analyzed the relative expression of six commonly used candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 40 publications
7
32
0
Order By: Relevance
“…In this study, host plants caused the most variations for the Ct values in A. viennensis. Similar studies in other arthropods, however, have not found such dramatically variations in Ct values (the cotton mealybug, P. solenopsis, Arya et al, 2017; and the green peach aphid, M. persicae, Kang et al, 2017). Our results suggest that host plants can cause significant changes on arthropods at the molecular level.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study, host plants caused the most variations for the Ct values in A. viennensis. Similar studies in other arthropods, however, have not found such dramatically variations in Ct values (the cotton mealybug, P. solenopsis, Arya et al, 2017; and the green peach aphid, M. persicae, Kang et al, 2017). Our results suggest that host plants can cause significant changes on arthropods at the molecular level.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, the selection of appropriate reference genes is critical in offsetting variations and biases (Lü et al, 2018). Recently, there has been a dramatic increase in studies of reference gene selection in the cell-content feeding arthropods, including Hemiptera ( Supplementary Table S3; Li et al, 2013;Yang et al, 2014Yang et al, , 2015bYuan et al, 2014;Shang et al, 2015;Koramutla et al, 2016;Ma et al, 2016;An et al, 2016;Yu et al, 2016;Arya et al, 2017;Kang et al, 2017), and three spider mites species (Sun et al, 2010;Niu et al, 2012;Yue et al, 2013;Yang et al, 2015a). Most of these studies in Tetranychidae species have focused on the expression patterns of reference genes under the impact of insecticide and developmental stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α-TUB is the main component of microtubules that form the cytoskeleton structure, which plays an important role in several eukaryotic cellular processes, including cell mobility and division, and intracellular trafficking 29 . Our results are consistent with previous studies reporting that α-TUB was stable for developmental stages, sexes, tissues, temperature and photoperiod stresses in Empoasca onukii 8 , among various tissues from Coleomegilla maculata 30 and Mythimna separata 24 , for different temperatures in Phenacoccus solenopsis 31 as well as for developmental stages, tissues and sexes in Hermetia illucens 32 . The RPL12 gene encodes a structural protein of ribosomes and is involved in protein translation 33 .…”
Section: Experimental Conditionsupporting
confidence: 93%
“…For example, GAPDH, β-TUB, CYP2, and 18s rRNA are often selected as reference genes. However, the expression levels of HKGs may vary between different species, and experimental conditions [21][22][23][24][25][26][27]. Thus, the selection of a stable reference gene has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%